The Influence of Halal Labels and Food Ingredients on Purchasing Decisions for Mikro, Small, Medium Enterprises Food Products in Madiun City - Febry Suryamado (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of halal labels and food ingredients on purchase decisions for food products in Madiun City. Indonesia, as the country with the largest Muslim population, shows an increasing demand for halal-certified products, with approximately 13 million products certified as of 2020. Halal labels not only ensure compliance with Islamic law but also build consumer trust. Additionally, health awareness leads consumers to prefer products made from natural ingredients, which play a significant role in purchasing decisions. This research employs a quantitative method through surveys of consumers in Madiun to identify the relationships between halal labels, ingredient quality, and purchase decisions. The results are expected to provide insights for Micro, Small, and Medium Enterprises in formulating effective marketing strategies and enhance understanding of the importance of halal certification in increasing competitiveness in the increasingly competitive food market. These findings are anticipated to assist for Micro, Small, and Medium Enterprises in Madiun in understanding Muslim consumer behavior and encouraging the adoption of better halal standards.